2022
DOI: 10.1037/tam0000171
|View full text |Cite
|
Sign up to set email alerts
|

Leakage warning behaviors for mass school violence: An analysis of tips reported to a state school safety tip line.

Abstract: Tip lines are a promising strategy for promoting school safety by creating a structured system where students, staff, parents, and community members can anonymously report safety concerns. To date, little is known about the characteristics of tips, how tips are reported, and what implications for practice can be developed from studying tip line data. We analyzed 228 tips collected over the course of 43 months by the SafeOregon tip line in which one or more persons were reported for signaling intentions or desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Reporting systems such as Sandy Hook Promise Say Something Anonymous Reporting system have been implemented in some K-12 schools and colleges and universities around the country. Over half of the public middle schools and high schools across the United States have implemented some type of reporting system, and about 10 states in the country operate their own state-level reporting system (Hendrix et al, 2022; Planty et al, 2020). These reporting systems, which are anonymous, have been a vital resource for people who want to report suspicious activity, but feel guilty and/or fear potential retaliation from the individual of which they are reporting (Hendrix et al, 2022; Lankford et al, 2019; Madfis, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reporting systems such as Sandy Hook Promise Say Something Anonymous Reporting system have been implemented in some K-12 schools and colleges and universities around the country. Over half of the public middle schools and high schools across the United States have implemented some type of reporting system, and about 10 states in the country operate their own state-level reporting system (Hendrix et al, 2022; Planty et al, 2020). These reporting systems, which are anonymous, have been a vital resource for people who want to report suspicious activity, but feel guilty and/or fear potential retaliation from the individual of which they are reporting (Hendrix et al, 2022; Lankford et al, 2019; Madfis, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While conducting research on school shooters, the U.S. Secret Service was also examining the preattack behaviors of these perpetrators (Abel et al, 2022; Vossekuil et al, 2004). This and other research focused on those identifiable and observable behaviors that perpetrators of mass violence commonly share to create a set of warning behaviors (Abel et al, 2022; Fein et al, 1995; Hendrix et al, 2022; Langman, 2009; Meloy, 2016; Meloy et al, 2001, 2012, 2014; Vossekuil et al, 2004). This continued research on preattack warning behaviors has supported that there is not a comprehensive “profile” of mass violence offenders, but there are observable behaviors that when identified by others could lead to intervention and prevention (Abel et al, 2022; Meloy et al, 2021).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of statewide tiplines revealed that over half of public middle and high schools in the U.S. use tiplines, though most (60%) have been in operation for less than three years (Planty et al, 2015). School principals surveyed about tiplines’ effectiveness felt that the tiplines were mostly effective, but that insufficient or untimely information made responding challenging (Hendrix et al, 2022; Planty et al, 2015). There is little information about usage patterns of tiplines across student demographic groups.…”
Section: Recommendations To Promote School Safetymentioning
confidence: 99%